Role of Rehabilitation Program in improvement of Health-Related Quality of Life in Patients with Spinal Cord Injuries - Seraphina V., Cressida W., Seraphina Y. (Academic Journal of Clinicians, 2025)
Background: Spinal cord injury (SCI) profoundly affects health-related quality of life (HRQoL), necessitating comprehensive rehabilitation strategies. Despite the potential benefits, the specific impact of multidisciplinary rehabilitation programs on HRQoL in individuals with SCI is not well established. ObjectiveThis study aims to assess the effect of a multidisciplinary rehabilitation program on HRQoL in individuals with SCI. Methods: A total of 60 participants with SCI were recruited and underwent a 12-week multidisciplinary rehabilitation program, which included physical therapy, occupational therapy, and psychological support. HRQoL was evaluated using the Short Form Health Survey (SF-36) before and after the intervention. Statistical analysis was performed to determine the significance of changes in HRQoL scores. Results: The findings revealed significant improvements in overall HRQoL scores, with notable enhancements in physical functioning, mental health, and social participation (p < 0.05). Participants reported increased satisfaction with their rehabilitation experience and greater engagement in daily activities. Conclusions: The multidisciplinary rehabilitation program significantly enhances HRQoL in individuals with spinal cord injury, underscoring the importance of integrated care approaches. These results advocate for the adoption of multidisciplinary strategies in rehabilitation settings to improve outcomes for individuals with SCI.